2019
DOI: 10.3390/rs11202401
|View full text |Cite
|
Sign up to set email alerts
|

RadCalNet: A Radiometric Calibration Network for Earth Observing Imagers Operating in the Visible to Shortwave Infrared Spectral Range

Abstract: Vicarious calibration approaches using in situ measurements saw first use in the early 1980s and have since improved to keep pace with the evolution of the radiometric requirements of the sensors that are being calibrated. The advantage of in situ measurements for vicarious calibration is that they can be carried out with traceable and quantifiable accuracy, making them ideal for interconsistency studies of on-orbit sensors. The recent development of automated sites to collect the in situ data has led to an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
134
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(135 citation statements)
references
References 39 publications
(49 reference statements)
1
134
0
Order By: Relevance
“…In the absence of a field team, network data can be used to determine surface reflectance. Data derived from the in situ instruments at RRV are accessible to the public via the on-line RadCalNet portal [4,5]. TOA radiances are available at a nadir-view angle, as well as the bottom-of-atmosphere reflectances.…”
Section: Vicarious Calibrationmentioning
confidence: 99%
“…In the absence of a field team, network data can be used to determine surface reflectance. Data derived from the in situ instruments at RRV are accessible to the public via the on-line RadCalNet portal [4,5]. TOA radiances are available at a nadir-view angle, as well as the bottom-of-atmosphere reflectances.…”
Section: Vicarious Calibrationmentioning
confidence: 99%
“…Numerous post-launch absolute calibration techniques have been developed over the past decades; they can be broadly classified as on-board and vicarious methods [33][34][35][36][37][38][39][40][41][42][43]. On-board absolute radiometric calibration technique relies on calibration devices such as calibration lamps.…”
Section: Absolute Calibrationmentioning
confidence: 99%
“…However, there is a reported limitation in using these data as they are provided only at nadir view, causing viewing an angle effect on the non-nadir viewing sensor [34]. To address this issue, Bouvet et al suggested an approach based on simulating off-nadir TOA reflectances to match the viewing angle of the sensor of interest [40].…”
Section: Radiometric Calibration Networkmentioning
confidence: 99%
“…The validation exercise in [39] compares surface reflectance with simulations over AERONET sites, using the atmospheric parameters measured by AERONET station. Since simulated data over AERONET sites are not available, the validation exercise presented in this paper uses the publicly available surface reflectance measurements on the RadCalNet sites [44] [45] as reference data. This RadCalNet reference data are compared with PACO BOA surface reflectance retrieved from Sentinel-2 satellite scenes.…”
Section: Surface Reflectance: Comparison To Radcalnet Sites Datamentioning
confidence: 99%
“…This RadCalNet reference data are compared with PACO BOA surface reflectance retrieved from Sentinel-2 satellite scenes. These sites provide measurements for a certain extended area, typically flat and approximately Lambertian [45]. Therefore, the BOA reflectance compared in this study does not include the application of any Bidirectional Reflectance Distribution at a surface.…”
Section: Surface Reflectance: Comparison To Radcalnet Sites Datamentioning
confidence: 99%